2021
DOI: 10.3389/fmars.2021.631354
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of a Remotely Operated Vehicle, a Drop Camera, and a Trawl in Capturing Deep-Sea Epifaunal Abundance and Diversity

Abstract: Deep-sea ecosystems provide services such as food, minerals, and nutrient recycling, yet baseline data on their structure is often lacking. Our limited knowledge of vulnerable deep-sea ecosystems presents a challenge for effective monitoring and mitigation of increasing anthropogenic threats, including destructive fishing and climate change. Using data from two stations differing in total epifaunal abundance and taxonomic composition, we compared the use of imagery collected by two non-invasive tools [remotely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…Apart from these ROV video transects in the northwestern part of the Bering Sea, almost all other biodiversity data regarding deep-sea megafaunal communities in this region have been obtained using extractive gear, such as trawls and corers (Rybakova et al, 2020). Extractive sampling methods are known to underestimate megafauna abundance and richness, and are not directly comparable with our data (Uzmann et al, 1977;Ayma et al, 2016;De Mendonca and Metaxas, 2021). Most other recent comparable studies evaluating epifauna densities using high-resolution image transects have focused on topographic features such as abyssal hills (e.g., Durden et al, 2015;Durden et al, 2020), manganese nodule fields (e.g., Simon-Lledóet al, 2020), or hydrothermal vents (e.g., Thornton et al, 2016).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Apart from these ROV video transects in the northwestern part of the Bering Sea, almost all other biodiversity data regarding deep-sea megafaunal communities in this region have been obtained using extractive gear, such as trawls and corers (Rybakova et al, 2020). Extractive sampling methods are known to underestimate megafauna abundance and richness, and are not directly comparable with our data (Uzmann et al, 1977;Ayma et al, 2016;De Mendonca and Metaxas, 2021). Most other recent comparable studies evaluating epifauna densities using high-resolution image transects have focused on topographic features such as abyssal hills (e.g., Durden et al, 2015;Durden et al, 2020), manganese nodule fields (e.g., Simon-Lledóet al, 2020), or hydrothermal vents (e.g., Thornton et al, 2016).…”
Section: Discussioncontrasting
confidence: 54%
“…Nonetheless, even early imaging methods were considered highly cost effective for surveying megafauna (Uzmann et al, 1977), often defined as those larger than 1 cm or so and that can be recognised in seafloor images (Rybakova et al, 2020). Image-based methods generally have higher positional accuracy and are less destructive (Diaz, 2004;Ayma et al, 2016;De Mendonca and Metaxas, 2021;Mizuno et al, 2022). They can also be implemented at long-term seafloor observatories to collect time-series data (Soltwedel et al, 2005;Taylor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that the erect 3D structure of these habitatforming species was not efficiently captured in dredges and trawls on the hard bottoms of the Mayotte volcanic island slopes; similarly for penatulids and actinarians which have been observed only in images along sedimented slopes of PNG. This fishing gear selectivity has already been mentioned for hard bottoms (Williams et al, 2015) and for soft bottoms (e.g., pennatulids, actinids) (Rice et al, 1982;Nybakken et al, 1998;de Mendonça and Metaxas, 2021). However, cnidarians and poriferans represent key groups in the benthic ecosystem functioning, because they can host a large diversity of associated fauna (Buhl-Mortensen et al, 2010;Beazley et al, 2013).…”
Section: Taxonomic Coverage and Resolutionmentioning
confidence: 66%
“…Bottom trawling is to date the most reliable stock assessment method for demersal resources (Ovando et al, 2022) but it's temporally intensive application would have a high environmental impact (e.g., Hiddink et al, 2006;Jamieson et al, 2013;Flannery and Przeslawski, 2015;Colloca et al, 2017;Costello et al, 2017;Sciberras et al, 2018;Rousseau et al, 2019;De Mendonca and Metaxas, 2021). Imagery-based sampling methods are still not as widespread (Bicknell et al, 2016), although they are successfully applied for gathering species composition and abundance data, for instance along usage of Baited Remote Underwater Video Stations (BRUVs), stereo-BRUVs (with stereo cameras for accurate fish sizing), and more recently Deep-BRUVS (for deep-water deployments; e.g., Langlois et al, 2018;Withmarsh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%